Cariprazine in Bipolar Disorder and Substance Use: A Dual Approach to Treatment? - Simone Pardossi; Alessandro Cuomo; Despoina Koukouna; Mario Pinzi; Andrea Fagiolini (MDPI AG, 2024)
Bipolar disorder (BD) is characterized by recurrent episodes of mania, hypomania, and depression and is often complicated by comorbid substance use disorders (SUDs). Up to 60% of individuals with BD experience SUDs, which exacerbate mood instability and increase the risk of rapid cycling, suicide, and poor clinical outcomes. Current treatment strategies, including lithium and valproate, show limited efficacy in treating both BD and SUD. Psychotherapeutic approaches such as cognitive behavioral therapy (CBT) offer benefits but lack a specific focus on substances such as cannabis and cocaine. Since there is still debate on how to treat this comorbidity, there is a need to find new therapeutic options; this mini-review examines the pharmacological properties of cariprazine and its emerging role in the treatment of comorbid BD and SUD. Cariprazine, an atypical antipsychotic with partial agonism at dopamine D2 and D3 receptors, has shown promise in treating both mood symptoms and cognitive dysfunction in BD. Its unique affinity for D3 receptors, which are involved in motivation and reward processing, may offer advantages in reducing drug craving. Clinical trials indicate that cariprazine effectively treats manic, depressive, and mixed episodes in BD with a favorable side effect profile, particularly at lower doses. Preliminary results suggest its potential to reduce craving and substance use in individuals with co-occurring BD and SUD. Therefore, cariprazine, with its unique pharmacodynamic mechanism, could be further studied for the treatment of BD in comorbidity with SUD. However, evidence on the role of cariprazine in the treatment of SUDs remains limited, based primarily on case reports and animal studies. Further research, including large-scale clinical trials, is needed to determine its full efficacy in this dual diagnosis.